Efficacy and safety of galantamine in the treatment of Alzheimer's Disease and Alzheimer's Disease with cerebrovascular (Mixed Dementia) (GAL-DEM-402) (Medical Journal of Indonesia, 2007)
This study was aimed to evaluate the efficacy and safety of Acetylcholinesterase Inhibitor Galantamine (Reminyl®) for patients with Alzheimer's Disease (AD) and Alzheimer's Disease with cerebrovascular Disease (AD+CVD or mixed Dementia). A 6-month open label observational study of Galantamine has been conducted on 28 patients with AD and AD+CVD patients. Primary endpoints were cognitive performance as assessed using the Mini Mental Scale Examination (MMSE), the Restricted Reminding Test), the Neuropsychology Assessment, the Clinical Dementia Rating (CDR) to assess global function and the Neuropsychiatric Inventory (NPI) to assess behavioral symptoms. Patients were also monitored for safety evaluation. Six month Galantamine group had a significant better outcome of cognitive performance, global function and behavioral symptoms compared with the baseline data as were assessed using the MMSE (p<0.05), the Restricted Reminding (p<0.05), the Neuropsychology Assessment (p<0.05), the CDR (p<0.05) and the NPI (p<0.05). Minimal adverse events (32%) were anorexia and nausea. It is concluded that Galantamine has a significant benefit to improve cognitive, global function, behavioral symptoms and only caused minimal adverse events. (Med J Indones 2007; 16:94-100) Keywords: Galantamine, alzheimer, cerebrovascular disease, dementia, AD, AD+CVD